2021
DOI: 10.1038/s41598-021-84520-2
|View full text |Cite
|
Sign up to set email alerts
|

White matter microstructure relates to motor outcomes in myotonic dystrophy type 1 independently of disease duration and genetic burden

Abstract: Deficits in white matter (WM) integrity and motor symptoms are among the most robust and reproducible features of myotonic dystrophy type 1 (DM1). In the present study, we investigate whether WM integrity, obtained from diffusion-weighted MRI, corresponds to quantifiable motor outcomes (e.g., fine motor skills and grip strength) and patient-reported, subjective motor deficits. Critically, we explore these relationships in the context of other potentially causative variables, including: disease duration, elapse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…Details regarding image processing of the diffusion-weighted images were previously published ( 10 ). Since WM abnormalities in DM1 appear to be global rather than tract-specific ( 9 , 10 ), we limited our analyses to cerebral WM FA consisting of all supratentorial WM. Note that tract-based comparisons of WM across groups in this sample were reported previously ( 9 ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Details regarding image processing of the diffusion-weighted images were previously published ( 10 ). Since WM abnormalities in DM1 appear to be global rather than tract-specific ( 9 , 10 ), we limited our analyses to cerebral WM FA consisting of all supratentorial WM. Note that tract-based comparisons of WM across groups in this sample were reported previously ( 9 ).…”
Section: Methodsmentioning
confidence: 99%
“…Myotonic dystrophy type 1 (DM1) is an autosomal dominant, multisystemic disease caused by an expansion of a CTG trinucleotide repeat in the 3′ untranslated region of the dystrophia myotonica protein kinase gene ( DMPK ; OMIM 160900). Abnormalities in white matter—as measured with fractional anisotropy (FA)—are one of the most replicated findings in adult-onset DM1 ( 1 8 ) and appear to be a global phenomenon rather than tract specific ( 9 ). For instance, our group showed that relative to controls, DM1 patients exhibited reduced FA and increased axial diffusivity and radial diffusivity across tracts ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Neurological involvement in the DM1 has aroused lots of interest in the recent years and several brain MRI studies have reported white matter lesions and brain atrophy (Minnerop et al, 2011;Baldanzi et al, 2016;Zanigni et al, 2016;Okkersen et al, 2017b;Koscik et al, 2021;Leddy et al, 2021;Lopez-Titla et al, 2021). Diffusion tensor imaging studies have demonstrated widespread white matter lesions with reduced fractional anisotropy (FA) and increased mean diffusivity in patients with DM1 compared with controls (Cabada et al, 2017;Yoo et al, 2017;van Dorst et al, 2019).…”
Section: Introductionmentioning
confidence: 99%